Centralization of the Educational Field in Applied Linguistics - Megherbi Kder (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
In this linguistic description, we attempt to examine the structure of the educational-learning process as a communicative act in which all of its constituent parts interact, including "the teacher, the learner, and knowledge," as well as the external environment. We also attempt to examine the degree to which this act is represented within the educational classes, given that the main objective is to acquire knowledge and skill that aims to achieve existence and an entity of language. The learner, in terms of persistence in connecting new knowledge with prior understanding, and fully utilizing the mental faculties by the axis of contemporary pedagogy "the learner" for research and balance, increasing his abilities, and ultimately benefiting him.